Estudo da distribuição dos casos de Diabetes Mellitus em Presidente Prudente - SP - Ortega, L. N.; Simões, Maria Jacira Silva [UNESP] (My University, 2006)
The main causes of illness and consequent death in patients affected by Diabetes Mellitus are the long-term complications. Depression can make it harder to control the level of glucose in the blood, as well as intensifying and worsening the clinical complications, thus reducing the quality of life. The aim of this study was to estimate the incidence of Diabetes Mellitus in Public Health Clinic in Presidente Prudente (SP) in patients enrolled in the Hiper-Dia Program. From October 2003 to July 2004, a descriptive survey was carried out. Data were obtained from doctor's records of 50 diabetes patients and also their answers to a specific questionnaire. The majority of the patients were female, had not completed elementary school, with a family income below five minimum wages, a nationally-defined amount related to the poverty line. It was observed that 24% of the patients had depression and 76% never followed a controlled diet. Pharmacological treatment was prescribed for 82% of the patients. Twenty-eight patients were receiving psyicological treatment, together with oral hypoglycemic agents. The glycated hemoglobin was measured in 68%. The association between depression and submission to treatment was not significant. No statistical association was found between the psychologically assisted patient's group and glucose control (p= 0.40), diet control (p= 0.37) and physical activities (p= 0.77). It was concluded that 24% patients had depression and the majority not under diet control, but 82% were under pharmacological treatment.

As complicações crônicas são as principais responsáveis pela morbimortalidade dos pacientes com Diabetes Mellitus. Sintomas depressivos estão relacionados a um controle glicêmico pior e conseqüente piora na qualidade de vida. O objetivo do presente estudo foi verificar a ocorrência do Diabetes Mellitus em uma Unidade Básica de Saúde do município de Presidente Prudente – SP, em indivíduos cadastrados no Programa Hiper/Dia do Serviço Municipal de Saúde local. Foi realizado um estudo descritivo, no período de outubro de 2003 a julho de 2004. Os dados foram obtidos através dos prontuários e questionário específicos, de 50 portadores de diabetes. A maioria dos pacientes era do sexo feminino, não tinha o ensino fundamental completo e a renda familiar inferior a cinco salários mínimos. A referência de ocorrência de depressão era de 24% e a dieta alimentar nunca era realizada por 76% dos pacientes. O tratamento farmacológico foi prescrito para 82% dos mesmos. Os medicamentos mais utilizados foram os hipoglicemiantes orais. A hemoglobina glicada foi realizada em 68% dos pacientes. Vinte e oito deles, faziam acompanhamento psicológico, representando 56% da amostra. Não houve diferença estatisticamente significante em relação a depressão e adesão ao tratamento (p= 0,40). Verificou-se associação não-significativa entre acompanhamento psicológico e controle glicêmico (p= 0,40), adesão à dieta alimentar (p= 0,37) e prática de atividade física (p= 0,77). Conclui-se que 24% dos pacientes apresentava depressão, a maioria não fazia dieta alimentar e a terapia medicamentosa foi prescrita para 82% deles.
Study of the distribution of cases of Diabetes Mellitus in the city of Presidente Prudente (SP,Brazil)
Keywords: Depression; Diabetes Mellitus; Glycemia (Index); glibenclamide; glucose; glycosylated hemoglobin; insulin; metformin; oral antidiabetic agent; adult; Brazil; controlled study; correlation analysis; depression; descriptive research; diabetes mellitus; diet therapy; dietary intake; female; glucose blood level; health program; health survey; human; major clinical study; male; medical record; morbidity; physical activity; prescription; prevalence; psychotherapy; public health service; questionnaire; socioeconomics